Detection of Antibodies and Confirmation of Mycobacterium avium Subspecies paratuberculosis Using Nested PCR in Bulk Milk Samples from Nakasongola and Sembabule Districts, Uganda. (16th December 2013) - Okuni, Julius Boniface; Oyo, Tony; Kisekka, Magid; Ochwo, Sylvester; Kalenzi Atuhaire, David; Afayoa, Mathias; Olaho-Mukani, William; Ojok, Lonzy
Abstract : Mycobacterium avium subspecies paratuberculosis (MAP) is an emerging pathogen in many livestock and wildlife populations around the world. Concerns range from the serious economic impacts on livestock productivity to its suspected role in the human inflammatory bowel disease syndrome. Milk and faeces of infected animals are the main vehicles through which the organism spreads from infected to susceptible hosts. In this study, a survey was done in Nakasongola and Sembabule districts of Uganda involving a total of seven dairy collection centres to determine the prevalence of antibodies to MAP in bulk milk samples. The milk was tested with a commercial ELISA kit for MAP testing in milk. Positive and suspicious milk samples were further tested using nested PCR. Of the 257 milk samples tested, 11 (4.3%) were positive and five (1.9%) were suspicious. All the ELISA positive and suspicious milk samples were positive using nested PCR. The results show that MAP infection occurs in cattle from the two districts and highlight the need for a paratuberculosis control program in these and other districts where MAP infection has been reported.